Formy wspierania kreatywności pracowników w firmach globalnych - Skalik, Jan (Forms of employees' creativity support in global companies, 2006)
The patterns that enable companies to get stable competitive advantage through creative initiative of employees are still searched by Polish managers. Such a solution can be found in global companies. The content of this article describes most frequently used methods of employees’ creativity elicitation used by famous global companies like Toyota, Ford or Philips.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 266-272